Analysis Of Influence Of Tourism And Branding Perceptions On Purchase Decisions (Study conducted in Chinatown as Halal Gastronomy in the City of Bandung) - Sagala, Evin Davinci; Ningsih, Caria; Turgarini, Dewi (Universitas Pendidikan Indonesia, 2019)
The purpose of this study is to be able to determine the effect of tourist perceptions and Branding on purchasing decisions in the Chinatown tourist destination in Bandung. The independent variables in this study are perception and branding, while the dependent variable of this study is the purchase decision. The research method used in this research is quantitative with descriptive and verification categories. The population of this study was 38,000 visitors with a sample of 270 respondents. The sampling technique used is nonprobability sampling with a purposive method. The data analysis technique used is multiple linear regression with assistive devicesSPSS 25.0 for Windows computer software. The results showed that perception and branding had a positive and significant effect on purchasing decisions in Bandung's Chinatown tourist destination, both partially and simultaneously.